posted by .

I need help with these two problems. I need to have all of the steps shown for full credit and I get lost along the way.

6x - 2y = 10
4x + 3y = 12
solve the system by elimination.

solve inequality
-2(2x-6)-4x>or equal to 3x-10 + 9

It's at this point in our lessons I keep losing my previous knowledge. I think I need time to let the previous knowledge sink in before moving on. However, that isn't acceptable.
Thanks for your help.

  • Algebra -

    Multiply the top equation by 3 and the bottom equation by 2. Then add the two equations. This will elimination the y term.

    -2(2x-6)-4x ≥ 3x-10 + 9

    -4x+12-4x ≥ 3x-10 + 9

    Combine like terms. It works just like an equation, except that multiplying/dividing by a negative value reverses the carat (e.g., > ot <).

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. algebra

    solve by substitution 5x-2y = -5 y - 5x = 3 could someone take a min a show me how to do this problem by steps so i can do the rest of my problems and wait a min so i may ask questions. I m failing my algebra class and desparately …
  2. Algebra again

    I don't understand how to do this problems: Solve for the variable r, C=2PIr (PI is the pi symbol thing then r is next to it) and this problem solve for the variable l, S=B+1/2Pl I know this is the same question, but I somewhat understand …
  3. Math

    Solve for x: 5/x+6+2/x^2+7x+6=3/x+1 5/x+5+2/(x+6)(x+1)=3/x+1 5(x+6)(x+1)/x+6+2(x+6)(x+1)/(x+6)(x1)=3(x+6)(x+1)/x+1 5(x+1)+2=3(x+6) 5x+5+2=3x+18 5x+7=3x+18 2x=11 x=11/2 or 5 1/2 is my method correct?
  4. Algebra

    I was given an answer to a question but what I really need are the steps to get there as I have other questions I need to answer the same way. Solve the equation w=Cr^-2 for r I was given r=C/w This equation is meant to figure out …
  5. algebra- FINAL UNIT!!

    Hi! My name is Jason, I needed help studying for tomorrow's test. The exam is on number problems. EX. One positive number is 4 times another. IF 240 is divided by each number, the greater quotient exceeds the lesser by 15. Find the …
  6. algebra 1b

    i need to know how to solve certain problems like this 4x=2y-10 x+2y=5 i need examples of this and shown to me step by step
  7. Algebra II

    Solve the given system by using a substitution method 9x-2y=3 3x-6=y If you could show the steps because I have 10 problems for homework and I just need an example Thanks
  8. Algebra 2

    Solve: 2-y=sqrt(y+4) I need all of the steps. I need this ASAP because this assignment is due tomorrow. Thanks
  9. Algebra 2

    Solve e^(2x-1)=3 I need all of the steps. I need this ASAP because this assignment is due tomorrow. Thanks
  10. Math C30

    Does anyone know a simple way to solve identity problems?

More Similar Questions